Effects of drugs on kinetic values of cytokines, adenosine deaminase and 13,14-dihydro-15-keto-prostaglandin f2α in endotoxemia: a different approach - Feray Altan; Muammer Elmas; Ayse Er; Kamil Uney; Gul Cetin; Bunyamin Tras; Enver Yazar (Eurasian Journal of Veterinary Sciences)
Aim: The objective of this study was to determine the effects of enrofloxacin (ENR), flunixin meglumine (FM) and dexamethasone (DEX) on kinetic values of cytokines, adenosine deaminase (ADA) and 13,14-dihydro-15-keto-prostaglandin F2a (PGM) in lipopolysaccharide-induced endotoxemia. Materials and Methods: Rats were divided into seven groups. To induce endotoxemia, lipopolysaccharide (LPS) was injected into all groups, including the positive control. The six other groups received the following drugs: ENR, FM, low-dose DEX, high-dose DEX, ENR + FM + low-dose DEX and ENR + FM + high-dose DEX. After the treatments, blood samples were collected at 0, 1, 2, 4, 6, 8, 12, 24, and 48 hours. Serum tumor necrosis factor alpha (TNFα), interleukin- 6 (IL-6), interleukin-10 (IL-10), ADA and plasma PGM levels were determined by ELISA. Area under the concentration time curve (AUC0-48), maximal concentration in plasma or serum (Cmax) and time to reach (tmax) values were determined by pharmacokinetic computer program. Results: ENR increased (p<0.05) AUC0-48 of PGM and decreased (p<0.05) AUC0-48 of IL-6, IL-10 and ADA, while FM decreased (p<0.05) AUC0-48 of IL-6 and ADA compared to LPS group. DEX alone and combined administrations caused the lower AUC0-48 of all values (p<0.05). Conclusion: Kinetic values, especially AUC, may be used for total evaluation of endotoxemia markers determined at different sampling times in same groups as a different and logical approach.